2016
DOI: 10.1007/s10753-016-0341-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of IL-22 on the Inflammatory Mediator Production, Proliferation, and Barrier Function of HUVECs

Abstract: The aim of this study was to investigate the effects of interleukin (IL)-22 on proliferation function and inflammatory mediator production and barrier function of human umbilical vein endothelial cells (HUVECs). The expression of mRNA was detected by RT-PCR. The proliferation ability of cells was evaluated using a cell counting kit assay. Real-time quantitative PCR and Western blot were used to detect the expression of inflammatory mediators. The endothelial barrier permeability was assessed by measuring perme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Here, we observed that human endothelial cells express IL-22R, suggesting that like IL-17, IL-22 may play a role in angiogenesis. Further support of this notion was recently provided by He et al, who reported that treating HUVECs with IL-22 caused an increase in proliferation, and Wu et al who observed a pro-survival effect of IL-22 on pulmonary microvascular cells in a model of lung injury [29,30]. We observed similar effects by IL-22 under high and low serum concentrations, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…Here, we observed that human endothelial cells express IL-22R, suggesting that like IL-17, IL-22 may play a role in angiogenesis. Further support of this notion was recently provided by He et al, who reported that treating HUVECs with IL-22 caused an increase in proliferation, and Wu et al who observed a pro-survival effect of IL-22 on pulmonary microvascular cells in a model of lung injury [29,30]. We observed similar effects by IL-22 under high and low serum concentrations, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…HUVEC cells were pretreated with lipopolysaccharide (LPS) for 4 h to generate endogenous ClO – . [ 28 ] Imaging Fc 2 ‐CBDP micelles showed that LPS‐treated cells exhibited ≈16‐fold signal enhancement than the untreated control (Figure 3c,e). Furthermore, after pretreating HUVEC cells with N ‐acetyl‐ L ‐cysteine (NAC; 1 m m ) as a ROS scavenger for 2 h, [ 3a ] the signal enhancement ratio only reached to ≈fourfold as compared with the LPS‐untreated control (Figure 3e).…”
Section: Resultsmentioning
confidence: 99%
“…Under resting conditions, the IL-22 receptor (IL-22R1 subunit) mainly locates on tracheobronchial epithelial cells and, to a lesser extent, on airway epithelial cells (large and small airways, but not parenchyma) (52). Of interest, recent data indicate that the IL-22 receptor is also expressed by (microvascular) endothelial cells, especially at alveolar sites (60,61). Although it has been suggested that neutrophil proteolytic enzymes might cleave the IL-22 receptor (62), its expression appears to increase during the course of influenza (at least at 21 days postinfection) to localize at the sites of parenchymal lung remodeling/repair (repairing alveoli) (52).…”
Section: Discussionmentioning
confidence: 99%